In a Neonatal Piglet Model of Intestinal Failure, Administration of Antibiotics and Lack of Enteral Nutrition Have a Greater Impact on Intestinal Microflora Than Surgical Resection Alone. (August 2017) - Levesque, Crystal L.; Turner, Justine; Li, Julang; Wizzard, Pamela; St Pierre, Benoit; Lim, David; Wales, Paul
Background : Data are limited on how short bowel syndrome (SBS) affects the healthy developing intestinal microbiome, with even less assessing different SBS anatomical surgical models. This study was conducted to describe the "ileal" and "colonic" microflora in 2 surgical models of SBS. Materials and Methods : Neonatal piglets (2–5 days old) underwent intestinal resection, leaving the ileum (JI anatomy, n = 6) or removing the ileum and ileocecal valve (JC anatomy, n = 5), or sham surgery (sham; n = 4). JI, JC, and sham piglets commenced parenteral nutrition on day 0 and received ampicillin and trimethoprim-sulfadoxine on days 0–4 for prevention of line sepsis. At day 7, ileal and colonic digesta were collected, and they were also collected from age-matched sow-fed piglets (n = 6). DNA extraction, sequencing, and annotation followed standard procedures. Results : Colonic and ileal bacterial genus diversity and relative bacterial abundance were greater ( P < .05) in sow-fed compared with JI, JC, and sham piglets; however, minor differences were observed in either location between sham, JI, and JC piglets and within the surgical model. In the colon, sow-fed piglets had higher ( P < .05) abundance of Lactobacillus (26%) and tended to have lower ( P = .06) abundance of Enterococcus (<.1%) than JI, JC, or sham piglets, in which Lactobacillus and Enterococcus abundance averaged <.1% and 9%, respectively. Conclusions : Intestinal resection reduces bacterial diversity in the large bowel, and the difference is associated with the presence/absence of the ileum and ileocecal valve. The lack of enteral nutrition and antibiotic administration (ie, sow-fed vs surgery) had a greater influence on the observed shift in diversity and relative abundance than intestinal resection.